Desenvolvimento de leitora RFID para pecuária de precisão - Cleiton Anderson Profilio dos Santos (2021)
Monitoring the cattle herd goes beyond simple identification. Using Radio Frequency IDentification (RFID) technology, it is possible to measure physiological parameters, such as body temperature, which allows inferences about the health status of the animal. This becomes more delicate with the gradual withdrawal of vaccination against foot-and-mouth disease, which in the state of Mato Grosso do Sul will be in 2021 (IAGRO, 2019). Therefore, it is necessary to adopt some technique that allows identifying the febrile state of the animal in a timely manner, separating it from the others and adopting the appropriate procedures. The Faculty of Computing (FACOM) and Embrapa Beef Livestock have developed transponders for measuring body temperature, and a constant difficulty is the lack of readers that work properly. The objective of this work is to develop an RFID reader compatible with ISO 11784 and ISO 11785 standards that can be installed at the place where animals pass, reading the tags (earrings, bolus and subcutaneous implant, among others) and sending the data via LoRaWAN , GSM/GPRS or Wi-FI to TagoIO platform, FTP server, MySQL database or Google Drive spreadsheet. Through a web interface it is possible to carry out all the equipment configurations. This will allow the equipment to be used in the most diverse locations. In addition, a low-cost product that is accessible to small and medium producers was developed. Keywords: precision livestock; RFID reader; embedded systems; multiconnectivity.